The role of the Context in the Translation - Ziyodullo Khabibullayevich Rakhmatullayev (Zien Journals, 2021)
When translating from English into Uzbek there are numerous problems with the choice of words because of the polysemy of the English language. Context plays an important role in selecting the desired value. Contextual values arise in the use of words in the speech, depending on the environment, and marketed under the influence of narrow, broad and extra linguistic context1 . Under the context of commonly understood language environment, which is used one or other linguistic unit. Thus, the context words are a collection of words, grammatical forms and con-constructions, which occurs in an environment that word.
Keywords: Micro context; wide context; grammatical forms; linguistic context